Di sebalik rundingan damai Hat Yai - Myzara Ab Fatta, 1958- (Shah Alam, Selangor : Grup Buku Krangkraf, 2015)
On history of peace negotiations between Malaysia government and Malayan Communist Party at Hat Yai, Thailand.
'Sebagaimana yang diceritakan oleh Dato' Mocktar Mahmud Baginda'--Cover.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid
Keywords: Malayan Communist Party -- History; Communism -- Malaya -- History; Malaya -- History -- Malayan Emergency, 1948-1990.; Malaysia -- Politics and government -- 1960-1990.